The Influence of Cooperation on the Development of Credit Resources Market for Agricultural Business Entities - Ruslan MUDRAK; Petro BECHKO; Valentyn BECHKO; Olexsander NEPOCHATENKO; Svitlana PTASHNYK (Communications of International Proceedings, 2020)
The article considers the problems of the influence of cooperation on the development of credit resources market for agricultural sector. The analysis of activity of agricultural goods producers of Cherkasy region on capacity of farmland, majority of which are small-scale, has been carried out. Due to limited access to credit resources on credit resources market in general and preferential lending, growth of tax burden in particular, small-scale agricultural companies are in a difficult financial situation, which makes it impossible for them to operate on the principles of self-financing and self-sufficiency. The solution to this problem is possible through the creation of production, service and credit cooperatives and on their basis – the Agrarian Bank. The basic principles of functioning of agricultural cooperatives have been studied. It has been determined that the development of credit cooperation in this sector of the economy is mainly through the prism of lending, while leveling other important functions that can contribute to the sustainable development of small-scale agrarian sector. The peculiarities of the development of agrarian cooperation in Ukraine have been revealed, and functioning of the information-consulting center for consulting farmers has been singled out in the structure of the rural cooperative. It has been found that cooperation is one of the key institutions that will improve the efficiency of agricultural economy.
Keywords: Cooperation; Cooperative Movement; Agricultural Cooperatives; Credit Cooperation.